2019
DOI: 10.1016/j.ecoleng.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration of a willow cultivar (Salix miyabeana SX67) grown in a full-scale treatment wetland

Abstract: Ce fichier a été téléchargé à partir de PolyPublie, le dépôt institutionnel de Polytechnique MontréalThis file has been downloaded from PolyPublie, the institutional repository of Polytechnique Montréal http://publications.polymtl.ca ManuscriptFrédette et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
1
25
1
1
Order By: Relevance
“…These characteristics include their non-edibility, their high nitrogen absorption capacity as well as their ability to absorb certain metals such as cadmium (Aronsson and Perttu, 2001). Willows have been used for a multitude of environmental applications, such as municipal effluent treatment (Dimitriou and Aronsson, 2011;Guidi Nissim et al, 2015;Hasselgren, 1998;Holm and Heinsoo, 2013;Larsson et al, 2003;Perttu and Kowalik, 1997), biosolids treatment (Dimitriou and Aronsson, 2004), landfill leachate treatment (Aronsson et al, 2010;Dimitriou and Aronsson, 2010), polluted groundwater (Guidi Nissim et al, 2014) and effluent total evapotranspiration Gill, 2014, 2016;Frédette et al, 2019;Gregersen and Brix, 2001) for more than twenty years. In recent years, it has also been shown that the use of willow beds has an interesting potential for the treatment of wastewater (Grebenschykova et al, 2017, Khurelbaatar et al, 2017, complete evapotranspiration of effluent (Frédette et al, 2019) and nutrient recovery (Rastas Amofah et al, 2012) in cold climate.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics include their non-edibility, their high nitrogen absorption capacity as well as their ability to absorb certain metals such as cadmium (Aronsson and Perttu, 2001). Willows have been used for a multitude of environmental applications, such as municipal effluent treatment (Dimitriou and Aronsson, 2011;Guidi Nissim et al, 2015;Hasselgren, 1998;Holm and Heinsoo, 2013;Larsson et al, 2003;Perttu and Kowalik, 1997), biosolids treatment (Dimitriou and Aronsson, 2004), landfill leachate treatment (Aronsson et al, 2010;Dimitriou and Aronsson, 2010), polluted groundwater (Guidi Nissim et al, 2014) and effluent total evapotranspiration Gill, 2014, 2016;Frédette et al, 2019;Gregersen and Brix, 2001) for more than twenty years. In recent years, it has also been shown that the use of willow beds has an interesting potential for the treatment of wastewater (Grebenschykova et al, 2017, Khurelbaatar et al, 2017, complete evapotranspiration of effluent (Frédette et al, 2019) and nutrient recovery (Rastas Amofah et al, 2012) in cold climate.…”
Section: Introductionmentioning
confidence: 99%
“…Water supply has been identified as one of the most important driving factors of ET across willow species [38,41]. The data graciously shared by PÉTROMONT INC. allowed us to establish that the water table fluctuated mainly between depths of 0.6 to 1.3 m. Moreover, the experimental site was situated at less than 300 m from the St. Lawrence River.…”
Section: Convective Transport Of Dissolved Chemicals Towards the Rootmentioning
confidence: 99%
“…However, since the last decades of the 20th century, this activity was progressively abandoned, leading to the rapid regeneration of riparian forests composed mainly of common alder (Alnus glutinosa) and willow (Salix atrocinerea). The expansion of tree-covered areas around the lagoons led to a decrease in water availability due to the large water volume extracted from the ground by these species due to evapotranspiration [29]. Finally, siltation has also been compounded by sediment contributions due to recurrent forest fires within the drainage basin of the lagoons, particularly in the Louro and Vixán areas.…”
Section: Evolution and Environmental Implications Of The Reduction Inmentioning
confidence: 99%